Tinjauan Yuridis Penegakan Hukum Terhadap Peredaran Narkotika di Kalangan Remaja Menurut Undang Undang Narkotika (Studi Kasus di Polres Aceh Timur)”. - Deny Albar (Universitas Islam Sumatera Utara, 2022)
The implementation of eradication and countermeasures by the East Aceh Police Resort through preventive and repressive measures. Preventive actions are carried out through socialization, counseling, approaches with families, communities and so on. This effort is a form of prevention carried out institutionally and in collaboration with community participation. Socialization and counseling about the dangers of drug abuse are a priority for the police so that repressive actions (actions of arrest) can be minimized.The disconnection of information from the public as a reporter is also an obstacle in efforts to eradicate and overcome drug abuse, so it is necessary to provide further information to the public about the dangers of drugs and provide encouragement for the public to dare to report if there are individuals who commit criminal acts of drug abuse.Legal counseling must use a fast and effective strategy, so that the public really understands the dangers of narcotics and will take anti-narcotics action. The application of severe criminal sanctions to perpetrators of crime will provide a deterrent effect and at the same time have an impact on the law of effect and its social impact, namely as a vehicle for public learning, so that people will be well aware of the importance of staying away from narcotics abuse. Keywords: East Aceh Police, Drugs, Youth